Moderate volume of high relative training intensity produces greater strength gains compared with low and high volumes in competitive weightlifters - Gonzalez-Badillo, J. J.; Izquierdo, M.; Gorostiaga, E. M. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to examine the effect of 3 volumes of heavy resistance, average relative training intensity (expressed as a percentage of 1 repetition maximum that represented the absolute kilograms lifted divided by the number of repetitions performed) programs on maximal strength (1RM) in Snatch (Sn), Clean & Jerk (C&J), and Squat (Sq). Twenty-nine experienced (>3 years), trained junior weightlifters were randomly assigned into 1 of 3 groups: low-intensity group (LIG; n = 12), moderate-intensity group (MIG; n = 9), and high-intensity group (HIG; n = 8). All subjects trained for 10 weeks, 4-5 days a week, in a periodized routine using the same exercises and training volume (expressed as total number of repetitions performed at intensities equal to or greater than 60% of 1RM), but different programmed total repetitions at intensities of >90-100% of 1RM for the entire 10-week period: LIG (46 repetitions), MIG (93 repetitions), and HIG (184 repetitions). During the training period, MIG and LIG showed a significant increase (p < 0.01-0.05) for C&J (10.5% and 3% for MIG and LIG, respectively) and Sq (9.5% and 5.3% for MIG and LIG, respectively), whereas in HIG the increase took place only in Sq (6.9%, p < 0.05). A calculation of effect sizes revealed greater strength gains in the MIG than in HIG or LIG. There were no significant differences between LIG and HIG training volume-induced strength gains. All the subjects in HIG were unable to fully accomplish the repetitions programmed at relative intensities greater than 90% of 1RM. The present results indicate that short-term resistance training using moderate volumes of high relative intensity tended to produce higher enhancements in weightlifting performance compared with low and high volumes of high relative training intensities of equal total volume in experienced, trained young weightlifters. Therefore, for the present population of weightlifters, it may be beneficial to use the MIG training protocol to improve the weightlifting program at least in a short-term (10 weeks) cycle of training.